2022
DOI: 10.1001/jamanetworkopen.2022.36384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Front-of-Package Information, Fruit Imagery, and High–Added Sugar Warning Labels on Parent Beverage Choices for Children

Abstract: ImportanceFruit drinks are widely consumed by young children, and many parents mistakenly believe that these drinks are healthy, potentially due to front-of-package claims and imagery. Research is needed on the influence of this marketing and how labeling regulations could change behavior.ObjectiveTo assess the effects of a front-of-package 100% vitamin C claim, fruit imagery, percentage juice and teaspoons of added sugar disclosures, and high–added sugar warnings on parents’ choices, knowledge, and perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Moreover, the present research shows that even when claims and fruit imagery were present on product packages, the disclosure corrected misperceptions about ingredients and healthfulness of sweetened drinks. Similar to our findings, previous research shows that warning labels were effective in reducing parents’ sugary drink selection for their children when added to packages that also contained fruit imagery and marketing claims (24) . Therefore, FOP disclosures alone may provide enough information to counteract common claims, such as ‘good source of Vitamin C’, ‘all natural ingredients’ and ‘no high fructose corn syrup’, that may lead caregivers to believe that sweetened children’s drinks are healthful choices for children (20) .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, the present research shows that even when claims and fruit imagery were present on product packages, the disclosure corrected misperceptions about ingredients and healthfulness of sweetened drinks. Similar to our findings, previous research shows that warning labels were effective in reducing parents’ sugary drink selection for their children when added to packages that also contained fruit imagery and marketing claims (24) . Therefore, FOP disclosures alone may provide enough information to counteract common claims, such as ‘good source of Vitamin C’, ‘all natural ingredients’ and ‘no high fructose corn syrup’, that may lead caregivers to believe that sweetened children’s drinks are healthful choices for children (20) .…”
Section: Discussionsupporting
confidence: 91%
“…These findings are similar to studies that have examined effects of warning labels. FOP warnings, including symbols to highlight 'high-in' ingredients to avoid or statements about health harms related to consumption, have been found to correct misperceptions about the healthfulness of fruit drinks and reduce selection for their children (24)(25)(26) . The results assessing caregivers' base-level understanding of ingredients in children's sweetened and unsweetened drinks when viewing packages without disclosures (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Government could require that warning labels be displayed on products high in nutrients of concern, as warning labels have been found to mitigate but not eliminate ‘health halo’ effects of nutrition-related content claims on product perceptions and preferences [ 20 , 26 , 42 ]. More specifically, studies with US parents have found that displaying added sugar warning labels on sugary snacks and drinks encourages parents to choose healthier options for their children [ 39 , 43 ]. Overall, available evidence suggests that stricter regulation surrounding the marketing and labelling of toddler foods needs to be introduced to protect parents against potentially misleading claims and encourage healthier choices.…”
Section: Discussionmentioning
confidence: 99%